Egyptian expert opinion for the use of sodium‐glucose cotransporter‐2 inhibitors in patients with heart failure with reduced ejection fraction. (3rd February 2022) - Abdelhamid, Magdy; Kandil, Hossam; Hassanin, Mahmoud; Shaheen, Sameh; Sobhy, Mohamed; ElEtreby, Adel; Hasan‐Ali, Hosam; Mahfouz, Hala; Nasr, Gamila; Shawky, Islam; Emil, Sameh; ElSetiha, Mohamed; et al.
Abstract: Sodium‐glucose cotransporter‐2 inhibitor (SGLT2i) in patients with type 2 diabetes reduces the risk of serious heart failure events, specifically the risk of hospitalization for heart failure, and cardiovascular death. The benefit is most apparent in patients with a heart failure with reduced ejection fraction (HFrEF). Dapagliflozin and empagliflozin reduced the risk of cardiovascular death and hospitalizations for heart failure in patients with established HFrEF, including those without diabetes. Considering the magnitude of the problem and the expected benefit on the target population, an Egyptian consensus document was conducted to demonstrate the importance of and the critical knowledge needed for effective and safe implementation of SGLT2i in the daily practice for the management of patients with HFrEF.